Cambridge practice tests for first certificate - Carne, Paul. (Tài liệu luyện thi chứng chỉ FCE., 2001)
Introduction; Study notes; Taking the exam; The practice tests; Key and tapescripts; Visual materials for the speaking test; Sample answer sheets.